Drivers of Meta-Banking Adoption: The Role of Perceived Value and Trust in Technology - Al-Mu’ani, Lu’ay; Altrjman, Ghaiath; Al Adwan, Ahmad; Tarawneh, Muath Ayman; Mahrakani, Nihaiah; Morshed, Omar; Nofal, Reema (Journal of Posthumanism, 2025)
This study investigates the determinants of consumers' intention to adopt meta-banking services, focusing on Perceived Value as a key mediator and Trust in Technology as a crucial moderator. Drawing on established technology acceptance theories, we developed a research model examining how Compatibility, Facilitating Conditions, Perceived Ease of Use, Perceived Enjoyment, Perceived Usefulness, Personal Innovativeness in IT, and Technostress influence Perceived Value, which in turn affects Adoption Intention. Data were collected via an online survey from 312 Jordanian consumers with prior AR/VR experience and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Results confirmed that all hypothesized factors significantly influence Perceived Value, with Technostress having a negative impact. Perceived Value strongly predicted Adoption Intention. Importantly, Trust in Technology positively moderated the relationship between Perceived Value and Adoption Intention. These findings provide theoretical insights and practical guidance for financial institutions developing meta-banking strategies.